Hydrogen Sulfide Overproduction Is Involved in Acute Ischemic Cerebral Injury Under Hyperhomocysteinemia - Ji, Yan; Li, Yusheng; Zhao, Zichen; Li, Panxing; Xie, Yi (Frontiers in Neuroscience, 2020)
Objectives This study aimed to identify the involvement of hydrogen sulfide overproduction in acute brain injury under ischemia/reperfusion and hyperhomocysteinemia. Methods In vitro and in vivo experiments were conducted to determine: the effect of sodium hydrosulfide treatment on the human neuroblastoma cell line (SH-SY5Y) under conditions of oxygen and glucose deprivation; the changes of hydrogen sulfide levels, inflammatory factors, energetic metabolism, and mitochondrial function in the brain tissue of rats under either ischemia/reperfusion alone or a combination of ischemia/reperfusion and hyperhomocysteinemia; and the potential mechanism underlying the relationship between homocysteine and these changes through the addition of the related inhibitors. Furthermore, experimental technologies, including western blot, enzyme-linked immunosorbent assay, immunofluorescence, reverse transcription polymerase chain reaction, and flow cytometry, were used. Results Our study found that high concentration of sodium hydrosulfide treatment aggravated the decrease in mitochondrial membrane potential, the increase in both mitochondrial permeability transition pore and translocation of cytochrome C, as well as the accumulation of reactive oxygen species in oxygen and glucose deprived SH-SY5Y cells. As a result, neurological deficit appeared in rats with ischemia/reperfusion or ischemia/reperfusion and hyperhomocysteinemia, and a higher water content and larger infarction size of cerebral tissue appeared in rats combined ischemia/reperfusion and hyperhomocysteinemia. Furthermore, alterations in hydrogen sulfide production, inflammatory factors, and mitochondria morphology and function were more evident under the combined ischemia/reperfusion and hyperhomocysteinemia. These changes were, however, alleviated by the addition of inhibitors for CBS, CSE, Hcy, H2S, and NF-κB, although at different levels. Finally, we observed a negative relationship between the blockage of: (a) the nuclear factor kappa-B pathway and the levels of cystathionine β-synthase and hydrogen sulfide; and (b) the hydrogen sulfide pathway and the levels of inflammatory factors. Conclusion Hydrogen sulfide overproduction and reactive inflammatory response are involved in ischemic cerebral injury under hyperhomocysteinemia. Future studies in this direction are warranted to provide a scientific base for targeted medicine development.